Impact of Patch Testing on Quality of Life in Patients with Hand Eczema: A Follow-up Study - Agrawal, S; Rijal, A; Bhattarai, S (Kathmandu University Medical Journal, 2015)
Background Patch testing has previously been shown to influence the quality of life, although a very few studies have shown if this is dependent on the result of the patch tests. Objective To assess the impact of patch testing on the quality of life (QOL) in patients with hand eczema (HE). Methods A total of 50 patients diagnosed of hand eczema at the time of patch testing, aged 16 years and above participated in this study. Detailed demographic information and diagnosis of hand eczema were collected on the day of the patch test. After six weeks, the patients were asked about the hand eczema, knowledge of their allergies and change in their life style to avoid the relevant allergens demonstrated on the patch test. Dermatology Life Quality Index (DLQI) was used to measure the QOL on both occasions. Results The patch test positivity was found in 68% of patients to one or more allergens. The sum score of DLQI at baseline was 12.16 ± 5.58 with median 12.0. HE had most impact on symptoms and feelings. Patients with both positive patch test (mean baseline= 11.94± 5.88; mean at six weeks=2.81± 2.01; P<0.001) and negative patch test (mean baseline=12.63± 5.03; mean at 6 weeks=5.4± 3.56; P=0.001) showed significant improvement in DLQI scores, however it was more improved in patients with positive patch test than in patients with negative patch test. Conclusions Hand eczema had an appreciable impact on the QOL. Patch testing had been beneficial to most patients in improving patient quality of life considerably. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12506 Kathmandu Univ Med J 2013; 43(3):216-220